2012
DOI: 10.1371/journal.pone.0043581
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Approach Identifies Multiple Genes and Signaling Pathways Downstream of Tbx4 in the Developing Allantois

Abstract: Loss of Tbx4 results in absence of chorio-allantoic fusion and failure of formation of the primary vascular plexus of the allantois leading to embryonic death at E10.5. We reviewed the literature for genes implicated in chorio-allantoic fusion, cavitation and vascular plexus formation, processes affected in Tbx4 mutant allantoises. Using this candidate gene approach, we identified a number of genes downstream of Tbx4 in the allantois including extracellular matrix molecules Vcan, Has2, and Itgα5, transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…A major finding in this study was that virtually all αSMA expressing myofibroblasts as well as COL1α1expressing fibro TGFβ-induced HA production in 3T3 mouse fibroblasts, suggest ing that Has2 is regulated by TBX4 ( Figure 10D) in agreement with results from the allantois (37). There are 3 putative Tbox response elements in the Has2 promoter (37).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A major finding in this study was that virtually all αSMA expressing myofibroblasts as well as COL1α1expressing fibro TGFβ-induced HA production in 3T3 mouse fibroblasts, suggest ing that Has2 is regulated by TBX4 ( Figure 10D) in agreement with results from the allantois (37). There are 3 putative Tbox response elements in the Has2 promoter (37).…”
Section: Discussionsupporting
confidence: 86%
“…There are 3 putative Tbox response elements in the Has2 promoter (37). Using a luciferase promoter assay, we showed that TBX4 could significantly induce the activ ity of vectors containing Has2 promoters ( Figure 10E), suggesting that TBX4 regulates Has2 through transcriptional regulation.…”
Section: Discussionmentioning
confidence: 95%
“…In line with this, homozygous T mutants die due to failure of allantois development; in mutants, the core fails to survive and the vascular network fails to form (Inman and Downs, 2006). A different T-box gene, Tbx4, is similarly required for allantois growth, vascularization and fusion with the chorion, although in Tbx4 mutants endothelial cells are formed but fail to undergo vascular remodeling (Arora et al, 2012a;Naiche and Papaioannou, 2003). A number of Tbx4 candidate target genes that are involved in chorio-allantoic fusion and vascular remodeling have been identified, indicating that Tbx4 affects a Box 1.…”
Section: Early Development Gastrulation and Somite Patterningmentioning
confidence: 91%
“…network of genes in the allantois (Arora et al, 2012a;Naiche et al, 2011;Naiche and Papaioannou, 2003). In contrast to T, Tbx6 is expressed in the presomitic mesoderm of the primitive streak and has several distinct effects on the specification and differentiation of the presomitic mesoderm, as well as on ciliogenesis in the node.…”
Section: Cip1mentioning
confidence: 99%
“…TNAP Cre is expressed in PGCs with a recombination efficiency of approximately 60%, and is expressed in the placenta after E10 [43]. Given the requirement for Tbx4 in the developing allantois [14,44], we were unable to use TNAP Cre to delete Tbx4 in PGCs. Prdm1-cre is expressed in 55%-76% of PGCs by E7.5 [45].…”
Section: Discussionmentioning
confidence: 99%